Modelos de cálculo de transporte en celdas. - Vázquez, Francisco M. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2011)
Fil. Vázquez, Francisco M.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina